Association of induction of labor and uterine rupture in women attempting vaginal birth after cesarean: a survival analysis - Harper, Lorie M.; Cahill, Alison G.; Boslaugh, Sarah; Odibo, Anthony O.; Stamilio, David M.; Roehl, Kimberly A.; Macones, George A. (American journal of obstetrics and gynecology, 2012)
We sought to estimate the risk of uterine rupture associated with labor induction in women attempting trial of labor after cesarean (TOLAC) accounting for length of labor. This was a nested case-control study of women attempting TOLAC within a multicenter retrospective cohort study of women with a prior cesarean. Time-to-event analyses were performed with time zero defined as the first cervical exam of 4 cm. Subjects experienced the event (uterine rupture) or were censored (delivered). In all, 111 cases of uterine rupture were compared to 607 controls. When accounting for length of labor, the risk of uterine rupture in induced labor was similar to the risk in spontaneous-onset labor (hazard ratio, 1.52; 95% confidence interval, 0.97–2.36). An initial unfavorable cervical exam was associated with an increased risk of uterine rupture compared to spontaneous (hazard ratio, 4.09; 95% confidence interval, 1.82–9.17). After accounting for labor duration, induction is not associated with an increased risk of uterine rupture in women undergoing TOLAC.